2003
DOI: 10.1038/nature01947
|View full text |Cite
|
Sign up to set email alerts
|

Genome divergence in two Prochlorococcus ecotypes reflects oceanic niche differentiation

Abstract: The marine unicellular cyanobacterium Prochlorococcus is the smallest-known oxygen-evolving autotroph. It numerically dominates the phytoplankton in the tropical and subtropical oceans, and is responsible for a significant fraction of global photosynthesis. Here we compare the genomes of two Prochlorococcus strains that span the largest evolutionary distance within the Prochlorococcus lineage and that have different minimum, maximum and optimal light intensities for growth. The high-light-adapted ecotype has t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
969
4
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,076 publications
(1,019 citation statements)
references
References 28 publications
43
969
4
3
Order By: Relevance
“…The first analyses of marine cyanobacterial genomes provided explanations for divergent patterns of depth distribution of ubiquitous primary producers , Palenik et al 2003, Rocap et al 2003. The first complete genome sequence of a marine 'heterotrophic' bacterioplankton species, Silicibacter pomeroyii, a member of the abundant Roseobacter clade, showed that it uses inorganic compounds like carbon monoxide and sulphide at concentrations found in the oceans to supplement heterotrophy (i.e.…”
Section: Novel Perspectives On Carbon Cycling From Genomicsmentioning
confidence: 99%
“…The first analyses of marine cyanobacterial genomes provided explanations for divergent patterns of depth distribution of ubiquitous primary producers , Palenik et al 2003, Rocap et al 2003. The first complete genome sequence of a marine 'heterotrophic' bacterioplankton species, Silicibacter pomeroyii, a member of the abundant Roseobacter clade, showed that it uses inorganic compounds like carbon monoxide and sulphide at concentrations found in the oceans to supplement heterotrophy (i.e.…”
Section: Novel Perspectives On Carbon Cycling From Genomicsmentioning
confidence: 99%
“…[9]. Recently, the genomes of three different members of the cyanobacterium species Prochlorococcus marinus have been sequenced [10,11]. These members of the genus Prochlorococcus dominate phytoplankton communities in most tropical and temperate open ocean ecosystems [12].…”
Section: Individual Organismsmentioning
confidence: 99%
“…P. marinus is found in two main ecological forms: high-light-adapted genotypes in the upper part of the water column and low-light-adapted genotypes at the bottom of the illuminated layer [10]. The analysis of the genome sequences of the different P. marinus strains led to the identification of genes, which play a role in determining the relative fitness of the ecotypes in response to key environmental variables [11]. Glöckner et al [13] reported the complete genome sequence of Pirellula sp.…”
Section: Individual Organismsmentioning
confidence: 99%
“…Analysis of the transcriptional networks showed that a total of 17, 21, 32 and 28 distinct transcriptional modules can be detected within the transcriptional networks of PMT, PMM, SYG and SYW, respectively (Additional file 2: Figure S2). More transcriptional modules detected in SYG and SYW than PMT and PMM were probably due to the relatively large genome sizes of Synechococcus [32][33][34]. The association analysis between the phenotypes (i.e.…”
Section: Construction Of Cyanobacteria Metal Response Networkmentioning
confidence: 99%
“…Therefore, we excluded all samples at 0 hour from our analysis. The updated genome annotation for all four species was downloaded from NCBI and the Comprehensive Microbial Resource (CMR) of TIGR (http://www.tigr.org/ CMR) [32][33][34]. KEGG Pathway and COGs (Cluster of Orthologous Groups of proteins) information was obtained from the KEGG Pathway Databases (http://www.…”
Section: Dataset Acquisitionmentioning
confidence: 99%